Fluoride Technology for Obtaining Magnetic Materials Based on Nd-Fe-B. Kinetics of Fluorination Processes of Neodymium and Iron Oxides; Procedia Chemistry; Vol. 11 : 1st International Symposium on Inorganic Fluorides: Chemistry and Technology, ISIF 2014, Tomsk, Russia - Sofronov V. L. Vladimir Leonidovich; Buinovsky (Buynovskiy, Buinovskii) A. S. Alexander Sergeevich; Makaseev Yu. N.; Smolkin P. A.; Ivanov Z. S.; Ermakova Ya. V. Yanina Viktorovna (2014, 2014)
Title screen